Difusão e distribuição espacial da Covid-19: desafios e potencialidades da atenção básica à saúde no ano de 2020 em Santa Maria, RS - Erthal, Douglas Bouvier (2023)
In the year 2020, the world was struck by an epidemic event that quickly evolved into a pandemic state. It was a new type of coronavirus (Covid-19), which became one of the greatest public health challenges in recent history. At this time, there was a concern to map and identify the spatial pattern of the virus, which followed from regions with higher densities of services and high flux of people to smaller ones. This evaluation took place not only on the scale of countries, but also in smaller ones, such as cities. Thus, the objective of this work was to identify the spatial pattern of Covid-19 diffusion in the intra-urban context of Santa Maria/RS and the challenges imposed for Primary Health Care services in the 2020 period. The information related to cases and deaths as a result of the disease were available through the Health Information Observatory of the Federal University of Santa Maria for the entire year 2020, in the pandemic emergency phase. We also used cartographic data related to the territorial organization of the municipality as well as to the AB. To identify the social conditions of the territory, the Social Deprivation Index (IPS) was used, which identified the poverty spots in the urban perimeter of the municipality. Information about the challenges of AB was collected through semi-structured interviews. The results showed that Santa Maria presented a spreading pattern of the diffusion by contagion type. All neighborhoods presented cases of Covid-19 in the year 2020, and factors such as age differentials and social deprivation were important for understanding the pattern of deaths from the disease. In the sense of AB, the interviews made it possible to show the main difficulties faced in the period, such as centralization of information, lack of human resources and adequate working conditions in health units.